Structural and Biochemical Dissection of the KMT2 Core Complex - Zhang, Pamela Peng (Université d'Ottawa / University of Ottawa, 2015)
Histone H3 lysine 4 (H3K4) methylation is an evolutionarily conserved mark commonly associated with transcription activation in eukaryotes. In mammals, this post-translational modification is deposited by the KMT2 family of H3K4 methyltransferases. Biochemical studies have shown that the enzymatic activity of the KMT2 enzymes is regulated by a core complex of four evolutionarily conserved proteins: WDR5, RbBP5, ASH2L and DPY30, collectively known as WRAD, which are all important for global H3K4 methylation. However, how these proteins interact and regulate the activity of the KMT2 enzymes is not well investigated. During my PhD, I have used structural and biochemical approaches to determine the interactions underlying formation of the core complex and regulation of KMT2 enzymatic activity. My research have shown that 1) WDR5 uses two peptide-binding clefts on opposite sides of its β-propeller domain to bridge the KMT2 enzymes to the regulatory subunit RbBP5, 2) the WDR5 peptidyl-arginine-binding cleft exhibits plasticity to accommodate the binding of all KMT2 enzymes and 3) RbBP5 S350 phosphorylation stimulates formation of the RbBP5-ASH2L complex and H3K4 methylation by the mammalian KMT2 enzymes. Collectively, these studies have provided the structural basis for understanding the important interactions governing KMT2 complex assembly and activity.
Keywords: Chromatin; Histone lysine methylation; X-ray crystallography